Recent advances of lab-based diffraction contrast tomography – reconstruction speed benchmark testing and validations. Issue 1 (1st July 2022) - Sun, J; Bachmann, F; Oddershede, J; Lauridsen, E
Abstract: Lab-based diffraction contrast tomography (DCT) enables the user to reconstruct 3D grain maps of polycrystalline materials non-destructively. For each grain, the morphology and crystallographic orientation, as well as derived properties such as grain boundaries, can be determined. Through two application examples this paper demonstrates the data acquisition and reconstruction speed of the current implementation and validates the resulting grain maps. Firstly, for a conventional Laue focusing scan of an AlCu sample comprising 340 grains, major performance enhancements of the reconstruction algorithm have reduced the reconstruction time from half a day to half an hour. The second example highlights an advanced scan with projection geometry of an oriented electrical steel sheet containing 7, 800 grains. While the data collection time is around a day for each of the data sets, the boosted reconstruction of the advanced acquisition data takes half a day and gives the full grain map without the need for stitching. After the major algorithm speed enhancements, grain map qualities are comparable with misorientations below 0.02° and grain boundary distances less than a voxel for both samples.